2005
DOI: 10.1007/s10764-005-8857-7
|View full text |Cite
|
Sign up to set email alerts
|

Soils Consumed by Chimpanzees of the Kanyawara Community in the Kibale Forest, Uganda

Abstract: We previously reported on a study of 4 soils that chimpanzees of the Kanyawara community in the Kibale National Park, Uganda consumed on a near-daily basis. We suggested that iron was a possible chemical stimulus in association with high quantities of Si:Al = 1:1-dominated clay minerals in the consumed material. To test our initial findings, we analyzed 18 samples from the same general area including 7 samples that the chimpanzees did not eat. Among the chemical elements, As, Au, Br, Ca, Cl, Dy, Mg, Ni, Sb, Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Finally, the ingestion of clay has often been linked to anaemia (Reid 1992) and worm infection (Luoba 2005), without any clear answer as to which is the cause or the effect. Soil eating is common in Kanyawara chimpanzees in the Kibale National Park, Uganda (Mahaney et al 1997(Mahaney et al , 2005. We observed that this consumption occasionally occurred very shortly after or before plant ingestion such as leaves of Trichilia rubescens.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Finally, the ingestion of clay has often been linked to anaemia (Reid 1992) and worm infection (Luoba 2005), without any clear answer as to which is the cause or the effect. Soil eating is common in Kanyawara chimpanzees in the Kibale National Park, Uganda (Mahaney et al 1997(Mahaney et al , 2005. We observed that this consumption occasionally occurred very shortly after or before plant ingestion such as leaves of Trichilia rubescens.…”
Section: Introductionmentioning
confidence: 80%
“…The geology of this area located on the East flank of the Ruwenzori Mountains, adjacent to a volcanic cone field, has been described by Mahaney et al (1997Mahaney et al ( , 2005. Chimpanzees of the Kanyawara community are fully habituated to the presence of observers since first observations started in 1983.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While mineral supplementation is widely considered to be one of the primary functions of geophagy in primates, it is almost impossible to determine which, if any, of these elements are targeted, especially as most are required in relatively minute amounts for a balanced diet. Avoidance of organic matter may also be a consideration here, considering the possible presence of harmful bacteria, although chimpanzees may not only be tolerant of such content [Mahaney et al, 2005], buy may seek it for specific medicinal properties [Ketch et al, 2001].…”
Section: Soil Composition and Functionmentioning
confidence: 99%
“…The most accepted hypotheses propose that soil (1) can help detoxify secondary plant metabolites and tannins [Gilardi et al, 1999;Johns and Duquette, 1991], (2) can provide supplementary minerals that might be absent or in very low concentration in an animal's diet [Oates, 1978;Brightsmith et al, 2008;Lee et al, 2009], (3) can act as an anti-diarrhoeal drug [Krishnamani and Mahaney, 2000] or (4) can be associated with the enhancement of the pharmacological properties of secondary plant compounds [Klein et al, 2008]. The higher concentration of minerals such as calcium, sodium or potassium, amongst others, from the mineral lick soils when compared to control sites [Emmons and Starck, 1979;Izawa, 1993;Montenegro, 2004;Mahaney et al, 2005], combined with the frequent use of mineral licks by many bird and mammal species, suggests that it has beneficial effects on their nutrition and health.…”
Section: Introductionmentioning
confidence: 99%